Local and global : social transformation in Southeast Asia : essays in honour of Professor Syed Hussein Alatas - Alatas, Hussein, Syed, 1928-2007; Hassan, Riaz, 1937-2022 (Social sciences in Asia ;, 2005)
The essays in this volume explore three aspects of social transformation of Southeast Asian Societies namely, social change and development, the role of intellectuals, religious and cultural values. They are a tribute to the seminal contributions of the distinguished Malaysian sociologist Syed Hussein Alatas.